Dampak Persaingan Bisnis Platform dengan Menggunakan Sarana Privacy Policy Tying (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2023)
The crucial role of personal data in the digital market has brought forth new challenges in competition law analysis, as exemplified by the case of privacy policy tying. This research aims to delineate the significance of personal data in competition law analysis and provide an analytical framework to assess the detrimental effects of privacy policy tying practices in order to ascertain their compliance with competition law. For that purpose, this research primarily focuses on two main aspects: the role of personal data in competition law analysis and the examination of the competitive impact in privacy policy tying cases. The research approach employed in this research is a normative legal approach, utilizing a literature review and qualitative analysis. Although personal data is not a tangible commodity subject to trade, it assumes a pivotal role as an intermediary product. It allows data controllers to extract essential information for tailored product customization to individual users. Privacy policy tying is utilized as a means to achieve this objective. This research posits that the analysis of the adverse impact of privacy policy tying practices in competition law primarily revolves around their exploitative and exclusionary elements, which undermine competition and harm consumers. Careful analysis is needed to avoid blurring the boundaries between competition law and personal protection, and impact analysis guidelines for cases involving the use of personal data AbstrakPeran penting data pribadi di pasar digital telah membawa tantangan baru bagi analisis hukum persaingan seperti yang ditunjukkan dalam kasus privacy policy tying. Penelitian ini bertujuan untuk mendeskripsikan bagaimana data pribadi berperan dalam analisis hukum persaingan dan menyediakan alat analisis untuk mengevaluasi dampak kerugian dalam praktik privacy policy tying untuk kualifikasi ilegalitas menurut hukum persaingan. Untuk tujuan tersebut, paper ini difokuskan pada dua persoalan pokok, yaitu bagaimana peran data pribadi berperan dalam analisis hukum persaingan dan bagaimana dampak persaingan dianalisis dalam kasus privacy policy tying. Penelitian ini menggunakan pendekatan normatif hukum dengan menggunakan studi pustaka dan analisis kualitatif. Meskipun data pribadi bukan komoditas dan tidak dapat diperdagangkan, namun ia memainkan peran penting sebagai produk antara yang memungkinkan perusahaan sebagai pengendali data untuk mengekstrak informasi penting guna penyesuaian produk bagi penggunanya secara individual. Privacy policy tying digunakan sebagai alat untuk tujuan tersebut. Paper ini berargumentasi bahwa analisis dampak negatif atas praktik privacy policy tying dalam hukum persaingan memusatkan perhatian pada elemen eksploitatif dan eksklusi dari praktik tersebut terhadap persaingan dan konsumen. Diperlukan ketajaman analisis untuk menghindarkan kekaburan batas-batas antara hukum persaingan dan pelindungan pribadi, dan suatu pedoman analisis dampak untuk kasus-kasus yang berkaitan dengan data pribadi.